IMPROVED LEARNING OUTCOMES OF MY FAMILY THEME WITH DEMONSTRATION LEARNING METHOD AT ELEMENTARY SCHOOL - Sri Suwartini (Ahlimedia Press, 2020)
This research is motivated by learning activities that occur in individuals who are complex behavior, because it is not only related to interactions between teachers and students, but also related to other learning components that support each other. To achieve the learning objectives, then the right method is needed in delivering learning material. The method applied by the teacher must be able to stimulate students to be active in learning activities. The problem examined in this study is how to improve learning achievement on the theme